2011
DOI: 10.1016/j.pcl.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Obesity in Children and Adolescents

Abstract: Synopsis The purpose of the present review is to provide a comprehensive update of current epidemiological studies that have assessed the association between sleep and obesity risk. Data from 29 studies conducted in 16 countries suggest that short sleep is associated with an increased risk for being or becoming overweight/obese or having increased body fat. Late bedtimes were also found to be a risk factor for overweight/obesity. Findings also suggest that changes in eating pathways may lead to increased body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 80 publications
(115 reference statements)
6
132
3
5
Order By: Relevance
“…Rather, we sought to illustrate some of the causes and consequences of adolescent sleep difficulties as well as to highlight some of the most recent findings in this area. Nonetheless, in order to limit the scope of this article we were unable to discuss sleep disorder diagnoses or several important research areas that are connected to adolescent sleep, including obesity (Guidolin and Gradisar 2012;Hart et al 2011), caffeine use (Bartel et al 2014;Roehrs and Roth 2008), the hypothalamic-pituitary-adrenal (HPA) axis and associated cortisol awakening response (CAR) (Elder et al 2014), cognition and memory (Beebe 2011;Kopasz et al 2010), and potential moderating factors such as sex and race/ ethnicity (Gregory and Sadeh 2012;Olds et al 2010). These too are clearly important areas for ongoing empirical attention and several articles in this Special Issue focus on these topics.…”
Section: Bit By Bit Putting It Togethermentioning
confidence: 99%
“…Rather, we sought to illustrate some of the causes and consequences of adolescent sleep difficulties as well as to highlight some of the most recent findings in this area. Nonetheless, in order to limit the scope of this article we were unable to discuss sleep disorder diagnoses or several important research areas that are connected to adolescent sleep, including obesity (Guidolin and Gradisar 2012;Hart et al 2011), caffeine use (Bartel et al 2014;Roehrs and Roth 2008), the hypothalamic-pituitary-adrenal (HPA) axis and associated cortisol awakening response (CAR) (Elder et al 2014), cognition and memory (Beebe 2011;Kopasz et al 2010), and potential moderating factors such as sex and race/ ethnicity (Gregory and Sadeh 2012;Olds et al 2010). These too are clearly important areas for ongoing empirical attention and several articles in this Special Issue focus on these topics.…”
Section: Bit By Bit Putting It Togethermentioning
confidence: 99%
“…Moreover, the association between low birth weight and the risk of childhood obesity is controversial. 7,8,10,[12][13][14][15][16][17][18] Several studies have suggested that maternal and child factors, such as maternal history of gestational diabetes, infant feeding mode, moderate-to-vigorous physical activity (MVPA), diet, sedentary and sleeping times may confound the association between birth weight and later risk of childhood obesity, 20-22 yet few studies were able to adjust for these factors simultaneously. Therefore, the aim of the present study was to examine the association between birth weight and the risk of obesity in 9-11-year-old children from 12 countries, adjusting for several confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies has shown an association between reduced sleep duration and childhood overweight, especially in young children. [1][2][3] The association between short sleep duration and overweight seems to be stronger for boys than girls, 4 although not all studies have reported a gender difference. 2 Possible explanations for the association between sleep duration and overweight include the role of behavioural and hormonal factors; short sleep leaves more time for eating, particularly snacking or drinking sugared drinks, and causes alterations in appetite-regulating hormones resulting in overeating.…”
Section: Introductionmentioning
confidence: 99%
“…10 The role of environmental factors on sleep duration is unclear, but there are indications that the physical and socio-cultural home environment play an important role. 3,11 A recent study among children aged 8-11 years suggested that less structure and rules in the home environment is associated with less sleep and more unhealthy behaviour, which is also associated with overweight. 11 It remains unclear whether the association between such family characteristics and unhealthy behaviours explain the association between sleep duration and overweight, or whether sleep duration and overweight are also associated independently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation